Endobronchial ultrasound-guided transbronchial needle aspiration: unraveling myths of mass in the chest - Wang, Rui; Zeng, Guangqiao (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Lung cancer is one of the most common neoplasms worldwide and a major cause of cancer death. Rapid diagnosis and accurate staging for patients with suspected lung cancer are essential to appropriate treatment. However, many of submucosal or parabronchial intrapulmonary lesions are invisible by bronchoscopy despite their adjacency to the central airway. Classical approaches in these cases, such as conventional bronchoscopy, transbronchial needle aspiration (TBNA) and computed tomography-guided transthoracic needle aspiration (TTNA), are of limited use in a sense of definitive diagnosis (1-3).